The “Great Game”: Mongolia between Russia And China - Her, Eric (Mongolian Journal of International Affairs, 2015)
No abstract available. DOI: http://dx.doi.org/10.5564/mjia.v4i0.421 Mongolian Journal of International Affairs Vol.4 2007: 62-71